Chemical Variability of Citrus maxima Essential Oils from South India - Kayikkarakottayil Varkey, Thankachan; Mathew, Joseph; Baby, Sabulal (Asian Journal of Chemistry, 2014)
Essential oils from the peels and leaves of Citrus maxima collected from five different geographical locations in south India were isolated by hydrodistillation. C. maxima peel and leaf oils were analyzed by the gas chromatography-mass spectrometry, constituents were identified by mass spectral database search, linear retention index data and comparison of mass spectra with literature. Twenty-two to twenty-five constituents (98.00-99.55 %) were identified in C. maxima peel oils. Major groups of compounds in C. maxima peel oils were monoterpene hydrocarbons (78.66-90.09 %), oxygenated monoterpenes (3.71-8.83 %) and sesquiterpene hydrocarbons (3.86-10.51 %). limonene (66.85-84.08 %), b-pinene (1.57-9.14 %), geranyl acetate (1.09-3.58 %) and verbenone (0.27-3.00 %) were the major constituents in C. maxima peel oils. Twenty-nine to thirty-five constituents (97.90-99.15 %) were identified in C. maxima leaf oils. Monoterpene hydrocarbons, oxygenated monoterpenes, sesquiterpene hydrocarbons and oxygenated sesquiterpenes in C. maxima leaf oils were (14.01-84.82, 6.47-50.41, 4.25-17.60 and 3.10-30.00 %), respectively. Limonene contents in C. maxima leaf oils were 5.29 to 78.45 %, with highest in the pathanamthitta accession. Other major constituents in C. maxima leaf oils were a-pinene (t-21.09 %) and b-pinene (t-16.93 %). Limonene with sesquiterpenes and their oxygenated derivatives in relatively minor quantities are the constituents giving flavour and aroma to C. maxima peel and leaf oils. Only limited variability was observed between the chemical profiles of the five C. maxima accessions from south India.